Correction to: Long-term patient reported outcomes following radiation therapy for oropharyngeal cancer: cross-sectional assessment of a prospective symptom survey in patients ≥65 years old. Issue 1 (December 2017) - Eraj, Salman; Jomaa, Mona; Rock, Crosby; Mohamed, Abdallah; Smith, Blaine; Smith, Joshua; Browne, Theodora; Cooksey, Luke; Williams, Bowman; Temple, Brandi; Preston, Kathryn; Aymard, Jeremy; et al.
Abstract In the original publication [1] the name of author Jeremy M. Aymard was spelled wrong. The original article was updated to rectify this error.